Local monomialization and factorization of morphisms - Cutkosky Steven Dale (Paris Societe Mathematique de France, 1999)
Suppose that R subset S are regular local rings of a common dimension, which are essentially of finite type over a field k of characteristic zero, such that the quotient field K of S is finite over the quotient field of R. If V is a valuation ring of K w
Keywords: Morphisms